ANALISIS KRITIS TENTANG POLEMIK IMAM ALGHAZALI DAN IBNU RUSYD TENTANG KEBANGKITAN JASMANI (Universitas PGRI Sumatera Barat, 2011)
Sritical analysis of the polemic of imam ghazali and Ibnu rusyd about the physical punishmenton the judgement day eventhough. Iman Al-ghazali and Ibnu rusyd have different ideals andarguments about the punishment all the judgement day, both of them have a great contribution tothe progress of Islamic thought. Rationally, it can be said that Ibnu rusdy has encounter Alghazalycriticsm, but from the affection of Islamic world, Al-ghazaly more powerful that Ibnurusdy. The latest philosopher is well know and he also called “hujjat al islam”.